KOORDINASI DALAM PEMELIHARAAN JALAN NASIONAL DI KOTA PEKANBARU - Putri, Nesvia; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Road is one of the most frequently used infrastructure by the society therefore its condition needs to meet the society’s expectation. The existence of good roads will facilitate the society to transport. Therefore the road should receive maintenance because the condition is often damaged in accordance to the Public Works Ministry Regulations No. 13 / KTR / 2011.Seeing how is the coordination in the maintenance of national roads. The purpose of this study to find out how coordination in the maintenance of national roads in the Center for the Implementation of the National Road II, Department of Highways Riau, and the Department of Highways and Water Resources Pekanbaru.In explaining the coordination of road maintenance in the Center for the Implementation of the National Road II, Department of Highways Riau, and the Department of Highways and Water Resources Pekanbaru, researcher used Malay Hasibuan’s theory which include : cooperation, communication, division of work and discipline.The results of this study showed that the coordination between the Center for the Implementation of the National Road II, Department of Highways Riau, and the Department of Highways and Water Resources Pekanbaru has been running well in terms of cooperation, communications, division of work and discipline, however due to some factors like estimate, truck overloading, and drainage the closed and clogged up that affect the sustainability of road maintenance that makes the work does not look as good as it seems and there are many roads that damaged after maintenance.Keyword : Coordination, Roads, Maintenance